1998
DOI: 10.2307/1592670
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing of Avian Escherichia coli Isolates by Random Amplification of Polymorphic DNA

Abstract: Escherichia coli is a common inhabitant of the gastrointestinal tract of most animals. Like most pathogenic E. coli, avian isolates cannot be distinguished biochemically from the normal commensals inhabiting the gastrointestinal tract of birds. Using a molecular approach, we were able to identify genetic differences among avian E. coli isolates by restriction fragment length polymorphism (RFLP) and random amplification of polymorphic DNA (RAPD) by the polymerase chain reaction (PCR). Several different RFLPs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 31 publications
8
39
0
Order By: Relevance
“…length polymorphism typing (Maurer et al ., 1998). The RAPD technique is simple, cheap, fast, requires only nanogram amounts of DNA and easily handles large numbers of samples (Ramasoota et al ., 2000;Chansiripornchai et al ., 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…length polymorphism typing (Maurer et al ., 1998). The RAPD technique is simple, cheap, fast, requires only nanogram amounts of DNA and easily handles large numbers of samples (Ramasoota et al ., 2000;Chansiripornchai et al ., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…(2000) found that RAPD analysis for typing E. coli isolates has the highest discriminatory capacity compared with serotyping and ribotyping. RAPD has also been used successfully to discriminate E. coli strains isolated from humans (Pacheco et al ., 1997;Hopkins & Hilton, 2001), cattle, swine (Ramasoota et al ., 2000;Aslam et al ., 2004) and avian species (Maurer et al ., 1998;Chansiripornchai et al ., 2001); Ramasoota et al . (2001) differentiated different clones inside the same E. coli serotype using RAPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are mosaic repetitive elements composed of various combinations of three subunit sequences referred to as boxA, boxB and boxC, with molecular lengths of 59, 45 and 50 nucleotides, respectively. Most of the fingerprinting techniques mentioned above were described by Louws et al [35] and have been applied for the analysis of antibiotic resistance genes [8,11,40]. RAPD and ERIC-PCR are generally much more discriminative than PFGE, distinguishing different genotypes among isolates considered as belonging to the same clone by PFGE.…”
Section: Arbitrarily Primed Pcr Multilocus Fingerprinting Methodsmentioning
confidence: 99%
“…The most commonly used molecular genetic fingerprinting technique is a restriction fragment length polymorphism (RFLP) analysis. Maurer et al, (1998) claimed that fingerprinting by RAPD revealed more genetic differences among avian E. coli strains than RFLP analysis. Akopyanz et al (1992); Makino et al (1994) and Pacheco et al (1996) observed that oligos with high GC content (>60%) resulted in a greater and better reproducible number of strain specific bands in enterotoxigenic E. coli.…”
Section: Discussionmentioning
confidence: 99%